Bat lung epithelial cells show variable species-specific susceptibility to human and avian influenza viruses - Slater, Tessa (2018)
The recent identification of two novel influenza-like viruses in bats, H17N10 and H18N11 virus, and the discovery of serologically positive Eidolon helvum bats in Ghana for avian H9 virus prompted my hypothesis that, in addition to the large repertoire of zoonotic viruses hosted, bats may serve as asymptomatic reservoir species to conventional influenza A viruses found in birds and mammals. To begin to test this hypothesis, the susceptibility of three bat cell lines, derived from lung epithelial cells of Eidolon helvum, Carollia perspicillata and Tadarida brasiliensis (TB1-Lu), to low pathogenicity avian viruses (H2N3 [A/mallard duck/England/7277/06] virus and H6N1 virus [A/turkey/England/198/09] virus), and human viruses (USSR H1N1 virus [A/USSR/77] and pandemic H1N1 2009 virus [A/California/07/2009]) was determined. All three species of bat epithelial cells were found to be more robust and resistant to influenza virus infections than permissive MDCK cells. Infected bat cells produced lower levels of viral RNA and viral progeny, and were more viable than correspondingly treated MDCK cells. Interestingly, bat cells were more susceptible and replication permissive to avian than human influenza viruses. Among the bat cells, TB1-Lu cells were the least susceptible to influenza virus infection and that appears to be related to a lack of sialic acid α2,6-Gal receptors, mammalian virus-preferred host receptors, which were present in the other two bat species. The innate mechanisms underlying resistance to influenza virus infection in bats remains to be determined, however, inhibition of the JAK/STAT pathway was found not to affect virus production from infected bat cells suggesting that JAK/STAT signalling may not have a major role in influenza virus resistance in bat cells. Modulation of NF-κB signalling was found to affect virus production suggesting that tight regulation of NF-κB may be key in controlling the pro-inflammatory response to influenza infection in bat cells and warrants further investigation.